Case report: A novel patient presenting TRIM32-related limb-girdle muscular dystrophy - Rimoldi, Martina; Romagnoli, Gloria; Magri, Francesca; Antognozzi, Sara; Cinnante, Claudia; Saccani, Elena; Ciscato, Patrizia; Zanotti, Simona; Velardo, Daniele; Corti, Stefania; Comi, Giacomo Pietro; Ronchi, Dario (Frontiers in Neurology, 2024)
Limb-girdle muscular dystrophy autosomal recessive 8 (LGMDR8) is a rare clinical manifestation caused by the presence of biallelic variants in the TRIM32 gene. We present the clinical, molecular, histopathological, and muscle magnetic resonance findings of a novel 63-years-old LGMDR8 patient of Italian origins, who went undiagnosed for 24 years. Clinical exome sequencing identified two TRIM32 missense variants, c.1181G > A p.(Arg394His) and c.1781G > A p.(Ser594Asp), located in the NHL1 and NHL4 structural domains, respectively, of the TRIM32 protein. We conducted a literature review of the clinical and instrumental data associated to the so far known 26 TRIM32 variants, carried biallelically by 53 LGMDR8 patients reported to date in 20 papers. Our proband's variants were previously identified only in three independent LGMDR8 patients in homozygosis, therefore our case is the first in literature to be described as compound heterozygous for such variants. Our report also provides additional data in support of their pathogenicity, since p.(Arg394His) is currently classified as a variant of uncertain significance, while p.(Ser594Asp) as likely pathogenic. Taken together, these findings might be useful to improve both the genetic counseling and the diagnostic accuracy of this rare neuromuscular condition.